A Theoretical-Practical Analysis of Philosophical and Psychological Aspects of Human Resources Management - Gevorgyan, Arusyak (Տիգրան Մեծ)
The article presents the role of human resources (HR) management philosophy in the work of an or-ganization. The staff management philosophy development phases, the principles and functions are ob-served. The link of HR management philosophy with the socio-cultural traditions and different countries and ethnic groups is shown based on the analyses of HR management national peculiarities. The author also represents the specifics of the HR management process in law enforcement bodies and in the Police of the Republic of Armenia in particular. The socio-psychological specifics of HR management in the Po-lice, as well as the perspectives of their development, are outlined
Keywords: Philosophy; Psychology